1993
DOI: 10.1007/bf01973689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subchronic administration of antioxidants against cigarette smoke exposure in rats

Abstract: Effects of subchronic administration of antioxidants against pulmonary damage mediated by cigarette smoke were investigated in rats. Rats were continuously received ascorbic acid, N-acetylcysteine and ginseng extract together drinking water from day 25 after birth. After 30 days of antioxidant supplementation, rats were exposed to cigarette smoke generated from six cigarettes (11 mg tar) for 20 min per day throughout 30 days, and then several biochemical markers related to the redox status in vivo were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…5 peroxidase activities, were increased in rats exposed to cigarette smoke. The mentioned study showed that using supplementation of antioxidants before smoking attenuated the harmful effects of cigarette on the pulmonary system; however, it was not enough to protect the organs completely (39). The current study revealed that salivary TAOC was higher in female than male subjects.…”
Section: Discussionmentioning
confidence: 48%
“…5 peroxidase activities, were increased in rats exposed to cigarette smoke. The mentioned study showed that using supplementation of antioxidants before smoking attenuated the harmful effects of cigarette on the pulmonary system; however, it was not enough to protect the organs completely (39). The current study revealed that salivary TAOC was higher in female than male subjects.…”
Section: Discussionmentioning
confidence: 48%
“…DPPH is one of the chromogen radical compounds that can directly react with antioxidants (22). When the DPPH radical is scavenged by antioxidants through donation of hydrogen to form a stable DPPH-H molecule, the color changes from purple to yellow (4,23). In the present study, the DPPH radicals were dose dependently scavenged by the various solvent extracts of ginseng in doses dependant ranging from 2 to 8 mg/mL.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 65%
“…It is most often used as a general tonic, and it involves a wide range of pharmacological actions, such as antiaging, adaptogen-like effects to foreign deleterious substances, immunoenhancement, antistress, antitumor, etc (1,2). Many of its effects have been attributed to its antioxidant action (3,4). In general, the pharmacological effects of ginseng roots have been attributed to ginsenosides, which are widely considered to be major components that contribute to the medicinal activities (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoke also generates ROS indirectly from activated polymorphnuclear leucocytes or pulmonary alveolar macrophages (2). The increased production of ROS by smoke can produce a condition of oxidative stress that can result in the oxidation of lipids, induction of DNA single-strand breakage, inactivation of certain proteins, and the disruption of biological membranes (12,24). Cigarette smoking is known to be associated with various chronic pulmoner and cardiovasculer diseases ranging from inflammation to cancer (4,5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Important antioxidant enzymes include copper (Cu) and zinc (Zn) superoxide dismutase (SOD), manganese SOD, ceruloplasmin (Cp), selenium glutathione peroxidase, glutathione reductase, and catalase. Non-enzymatic antioxidants include vitamin C, α-tocopherol, provitamin A carotenoids, and urate can also act to reduce of free radicals (10,13,24).…”
Section: Introductionmentioning
confidence: 99%